Analisis Pengaruh Profitabilitas, Likuiditas dan Leverage Terhadap Financial Distress - Rizky Aprilia; Fauzan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Financial Distress or financial difficulties are financial conditions in a company that are in trouble, crisis, or unhealthy before the company goes bankrupt. Financial can occur because a company fails or is unable to fulfill debtor obligations due to a lack or insufficient funds to run its business anymore. This study aims to see whether or not there is an influence of profitability, liquidity, and leverage on transportation companies listed on the Indonesia Stock Exchange from 2019 to 2022. The population used in this study were transportation and logistics companies listed on the Indonesia Stock Exchange as many as 37 companies. This study uses a purposive sampling method in sampling. The number of samples obtained was 21 companies in the observation period. The method in this study is by indirect observation by collecting data on the annual financial reports of transportation companies listed on the Indonesia Stock Exchange for the period 2019 to 2022. The analysis technique used in this study is multiple linear regression analysis. The results of the study show that the profitability, liquidity and leverage ratios have an effect on financial distress. This shows that the high and low ratios of profitability, liquidity, and leverage can affect financial distress in transportation companies listed on the Indonesia Stock Exchange.